Social Perception of Health and Illness - Carnazzola, Maria Grazia (Formazione & insegnamento, 2022)
In this time in which we feel suspended between the fourth industrial revolution and a pandemic that frightens us, we need more than ever an ethic of trust, of positive passions, of moving between normativity and fluidity without cynicism or indifference, each of us taking charge of change. This is the ethical task of education. The School must confront these positions and these arguments, using disciplinary knowledge to transform them first into knowledge, then into awareness and behavior. Only in this way, I believe, can we attempt to make individuals the true protagonists in the management of health and illness, because in relying on the myth of healing we are precluded from giving meaning to suffering, health and well-being.